Attitude to religion or religious identification among adolescents - Kabidenova, Zh. D.; Rysbekova, Sh. S. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
The article considers the analysis of studies religion and religious identification of adolescents in the light of issues need to support social and cultural space in the country and on the global situation in relation to the Central Asian region. Studied such aspects as the relation of religion and its role in society, religious tolerance, interest in any particular religion, the knowledge of new religious movements, as well as the importance of citizenship.Accordingly, according to the purpose of article authors to ask questions about that problem as the formation and strengthening of the religious identity as a cultural code of the rising generation is under a solid foundation. Modern realities of the postmodern age present before each state challenges that require decisions be put off, as it becomes quite difficult to maintain a national identity sociocultural space.Today, the importance of supporting social and humanitarian sector in education, and in particular the areas of religion and culture is important.